2020
DOI: 10.1111/1462-2920.15092
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbes of an urban remnant riparian zone have greater potential for N removal than a degraded riparian zone

Abstract: Summary Soils in the riparian zone, the interface between terrestrial and aquatic ecosystems, may decrease anthropogenic nitrogen (N) loads to streams through microbial transformations (e.g., denitrification). However, the ecological functioning of riparian zones is often compromised due to degraded conditions (e.g., vegetation clearing). Here we compare the efficacy of an urban remnant and a cleared riparian zone for supporting a putative denitrifying microbial community using 16S rRNA sequencing and quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Our findings are in accordance with Hartmann et al (2014), who found soil compaction induced by logging operations provoked lower microbial abundances but increasing bacterial and fungal diversity associated with new niches related to anoxic habitats. In this sense, families with anaerobiosis characteristics Hyphomicrobiaceae, Hyphomonadaceae (Middleton et al, 2020), Syntrophobacteraceae (Liu and Conrad, 2017), or Kouleothrixaceae (Astorga-Eló et al, 2020) were more abundant in soils under SL management than in soils under C management. In addition to the soil physical deterioration, the depletion in C and N compounds as a consequence of the erosion triggered by the SL reduced the microbial populations sensitive to substrates availability (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our findings are in accordance with Hartmann et al (2014), who found soil compaction induced by logging operations provoked lower microbial abundances but increasing bacterial and fungal diversity associated with new niches related to anoxic habitats. In this sense, families with anaerobiosis characteristics Hyphomicrobiaceae, Hyphomonadaceae (Middleton et al, 2020), Syntrophobacteraceae (Liu and Conrad, 2017), or Kouleothrixaceae (Astorga-Eló et al, 2020) were more abundant in soils under SL management than in soils under C management. In addition to the soil physical deterioration, the depletion in C and N compounds as a consequence of the erosion triggered by the SL reduced the microbial populations sensitive to substrates availability (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Among the families with recognized functions, bacteria associated with anaerobic respiration significantly increased in SL soils, highly represented by Gram-negative bacteria (Fraterrigo et al, 2006). Bacteria families with these characteristics in SL soils were the nitrate reducers and denitrifiers Hyphomicrobiaceae and Hyphomonadaceae (Alphaproteobacteria) (Middleton et al, 2020); the sulfate reducers in anoxic environments Syntrophobacteraceae (Deltaproteobacteria) (Liu and Conrad, 2017); the anoxygenic but potential N fixer Chloroflexaceae (Chloroflexi) (Xun et al, 2018); and Kouleothrixaceae (Chloroflexi), carbon degrader in anoxygenic environments (Astorga-Eló et al, 2020). Induced by the stressful conditions after SL performance, the families radiation-resistant Deinococcaceae and Trueperaceae (Thermo) prospered (Maier et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, nitrification-related genera (such as Nitrosomonas and Nitrospira) were positively correlated with DO. Periodic saturation of wetland sediments due to significant changes in seasonal streamflow would create fluctuating oxic/anoxic conditions for ammonium nitrification by Nitrosomonas and subsequent nitrite oxidation by Nitrospira, which is vital for nitrogen retention [40]. Therefore, the seasonal shock loads contributed to a unique community of the nitrogen-related microbes, which benefited the favorable nitrogen removal in the lakeshore MCW.…”
Section: Effects Of Seasonal Parameters On the Microbial Communitymentioning
confidence: 99%
“…The lake littoral zone is periodically exposed to water due to water level fluctuations, which are critical in shaping the hydrological characteristics of the ecotone [7]. The dynamic hydrologic connectivity resulting from these fluctuations causes the periodic drying and rewetting of ecotone soil and sediment, creating highly heterogeneous conditions with oxic-anoxic alternations [8]. This environmental variation, coupled with changes in the microbial community, affects the degree of the biogeochemical transformation of various nitrogen compounds in the lake littoral zone [9].…”
Section: Introductionmentioning
confidence: 99%